2019
DOI: 10.1016/j.yclnex.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial on the effects of CitrusiM® (Citrus sinensis (L.) Osbeck dried extract) on body composition

Abstract: Objective: In this report, we investigated the effects of CitrusiM® (Citrus sinensis (L.) Osbeck dried extract) on body composition, defined in terms of two outcomes: percentage of lean mass and percentage of fat mass. Research methods & procedures: A double-blind randomized experiment with overweight and obese volunteers was conducted in which the two variables were measured at baseline and three months afterwards. The treatment levels corresponded to three different daily doses of CitrusiM ® : 0 mg (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Additionally, the same treatment in 3T3-L1 adipocytes determined a reduction of lipid droplets regulating adipogenesis and thermogenesis via AMP-activated protein kinase alpha (AMPKα) pathway (Park et al, 2019). Kegele et al (2019) investigated the effects of CitrusiM® (Citrus sinensis dried extract) on body composition: percentage of lean mass and percentage of fat mass. This extract determined a significant reduction of fat, and increase in lean mass reducing waist circumference after a dose of 0.5 or 1 g/day.…”
Section: Antibacterial Potentialmentioning
confidence: 99%
“…Additionally, the same treatment in 3T3-L1 adipocytes determined a reduction of lipid droplets regulating adipogenesis and thermogenesis via AMP-activated protein kinase alpha (AMPKα) pathway (Park et al, 2019). Kegele et al (2019) investigated the effects of CitrusiM® (Citrus sinensis dried extract) on body composition: percentage of lean mass and percentage of fat mass. This extract determined a significant reduction of fat, and increase in lean mass reducing waist circumference after a dose of 0.5 or 1 g/day.…”
Section: Antibacterial Potentialmentioning
confidence: 99%
“…It has been suggested that anthocyanins provide protection against oxidative stress, coronary heart diseases, certain cancers, and other age-related diseases (Amorini et al 2003;Shu et al 2023). Dry extract of the Moro orange juice is widely used as a food supplement for disease prevention and obesity control, as investigated by in vivo (Titta et al 2010) and clinical studies (Cardile et al 2015; Kegele et al 2019). Its possible anti-in ammatory activity, and its potential to improve endothelial function and reduce in ammation in nondiabetic subjects with increased cardiovascular risk, have also been demonstrated (Buscem et al 2012).…”
Section: Introductionmentioning
confidence: 99%